2018
DOI: 10.1055/s-0038-1667381
|View full text |Cite
|
Sign up to set email alerts
|

Medical Ethics Education for Neurology Residents: Where Do We Go from Here?

Abstract: Neurologists regularly confront complex clinical scenarios that require the application of ethical principles to achieve a respectful and fair resolution. In this article, we describe the types of ethically precarious scenarios neurologists encounter, the current status of standards for ethics and communication training for neurology residents, and the present practice of ethics training in neurology residency programs. We make recommendations for optimizing bioethics training for neurology residents and sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…According to a recent study, the necessity of medical ethics courses given in medical faculties was reported, but it was reported that there was no standardization regarding the duration of medical ethics courses to be given (4). Similar results have been shown in other studies (14). According to another study, it was concluded that medical ethics education in medical school education significantly changed the students' perspective on medical ethics (15).…”
Section: Discussionmentioning
confidence: 77%
“…According to a recent study, the necessity of medical ethics courses given in medical faculties was reported, but it was reported that there was no standardization regarding the duration of medical ethics courses to be given (4). Similar results have been shown in other studies (14). According to another study, it was concluded that medical ethics education in medical school education significantly changed the students' perspective on medical ethics (15).…”
Section: Discussionmentioning
confidence: 77%
“…A qualitative study conducted to analyse the perspectives of US paediatricians regarding shared decision-making in ADHD showed that instead of familiarizing families with all the options first, the paediatricians provided information to persuade families to accept the treatment of their choice [ 70 ]. These different scenarios can be explained in part by the quality of communication between the physician and the patient/parent, the technical language used, and possibly the cultural context of both parties [ 71 ] as well as the development of medical bioethics and doctor–patient communication skills [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study conducted to analyse the perspectives of U.S. paediatricians regarding shared decision-making in ADHD indicated that instead of familiarizing families with all the options rst, the paediatricians provided information to persuade families to accept the treatment of their choice [73]. These different scenarios can be explained in part by the quality of communication between the physician and the patient/parent, the technical language used and possibly the cultural context of both parties [74] as well as the development of medical bioethics and doctor-patient communication skills [75].…”
Section: Discussionmentioning
confidence: 99%